Studies on the syngeneic mixed lymphocyte reaction. III. Development of a monoclonal antibody with specificity for autoreactive T cells (The Rockefeller University Press, 1983)
Monoclonal antibodies with specificity for autoreactive murine T cells have been developed. These antibodies inhibit proliferative response of splenic T cells activated by syngeneic spleen cells. These antibodies have no effect on the proliferative response of T cells activated by allogeneic spleen cells or PHA. The number of splenic T cells that react with these monoclonal antibodies is comparable in several normal mouse strains.